2016
DOI: 10.3174/ajnr.a4886
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Abnormalities in the Hippocampus of Patients with Schizophrenia: A 3D Multivoxel MR Spectroscopic Imaging Study at 3T

Abstract: BACKGROUND AND PURPOSE Schizophrenia is well known to be associated with hippocampal structural abnormalities. We used 1H-MRS imaging to test the hypothesis that these abnormalities are accompanied by NAA deficits, reflecting neuronal dysfunction, in patients compared with healthy controls. MATERIALS AND METHODS Nineteen patients with schizophrenia (11 male, 40.6±10.1 years old, 19.5±10.5 years disease duration) and 11 matched healthy controls (5 male, 33.7±10.1 years old) underwent MRI and multi-voxel point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
(54 reference statements)
1
15
0
1
Order By: Relevance
“…Using a novel multi-voxel, whole hippocampal 1 H-MRSI to assess metabolite concentrations in the entire bilateral 3-dimensional structure (as opposed to single voxel approaches), our prior study demonstrated only elevated Cr concentrations [Cr] signi cantly distinguish the group of cases from the control groups (11). Notably, concentrations of Cho and NAA in this study were signi cantly more variable within the group of cases than controls, consistent with heterogeneous underpinnings among schizophrenia cases.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…Using a novel multi-voxel, whole hippocampal 1 H-MRSI to assess metabolite concentrations in the entire bilateral 3-dimensional structure (as opposed to single voxel approaches), our prior study demonstrated only elevated Cr concentrations [Cr] signi cantly distinguish the group of cases from the control groups (11). Notably, concentrations of Cho and NAA in this study were signi cantly more variable within the group of cases than controls, consistent with heterogeneous underpinnings among schizophrenia cases.…”
Section: Introductionsupporting
confidence: 49%
“…Schizophrenia cases with rare missense coding variants in Trio Rho Guanine Nucleotide Exchange Factor (TRIO) or its interaction partner ARMS/Kidns220, had signi cantly lower [Cho] than other schizophrenia cases in this series and compared to the healthy control group in the parent study (11). TRIO is associated with autism and intellectual impairment in addition to schizophrenia (15)(16)(17), and this analysis suggests that these cases have signi cantly reduced hippocampal myelin.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Though some single-voxel studies have reported increased t-Cr [ 32 , 33 ], these have not been replicated [ 34 ]. However, an 1 H-MRSI study of the hippocampus revealed increased t-Cr in chronically-medicated schizophrenia [ 35 ]. We found increased t-Cr only in antipsychotic-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is often done by linear regression (Hetherington et al, 1996;Tal, Kirov, Grossman, & Gonen, 2012) or spectral decomposition methods (Goryawala, Sheriff, Stoyanova, & Maudsley, 2018), which combine information from multiple voxels with knowledge of the relative tissue content in each voxel. Linear regression can be applied in any number of (n≥2) voxels to investigate small regions such as the hippocampus (<10 voxels; Meyer et al, 2016), larger areas such as 2D slabs (McLean et al, 2000;Gasparovic et al, 2011), in entire brain lobes (Maudsley et al, 2009), and/or in global brain white matter/gray matter metabolism (100s of voxels; Tal et al, 2012). It is especially useful for studying cortical gray matter, which due to its tortuous shape, always incurs voxel partial volume effects when examined with SVS.…”
Section: Mr Spectroscopic Imaging (Mrsi)mentioning
confidence: 99%